Exploring the relationship between body mass index and facial crease among adult female: a scoping review - Anuar, Puteri Nurul Hassanah (2020)
The depth of facial crease and location of the facial crease may differ among different individuals which makes it a unique characteristic of an individual; hence this may affect the human identification process for forensic cases. Previous studies stated that thin people and women tend to have higher skin extensibility as compared to those who are fat and men. However, no studies have proven the relationship between body mass index (BMI) and facial wrinkle. Thus, this study is to review the studies examining the association between facial crease and BMI among females aged 40 and 60 years old. Articles were selected using PRISMA guidelines and several mainstream databases, such as Google Scholar, PubMed, Science Direct and Wiley Online were searched. A total of 20 articles were finally included and analysed. Findings revealed that BMI is associated with facial wrinkles though other parameters such as age, lifestyle, and sun exposure need to be considered as well. This parameter alone is a weak parameter to relate the facial wrinkles and skin ageing with body mass index. Other than that, intrinsic and extrinsic factors also need to be considered in analysing facial wrinkles and skin ageing.